Achieving our highest potential through character development (Husn-i-Akhlaaq): an Islamic perspective on holistic personality development, spiritual growth and human flourishing - Gillani, Uzma; Khan, Muhammad Jahanzeb (Frontiers in Psychology, 2025)
This article proposes a theoretical framework for human personality development based on Husn-i-Akhlaaq, the Islamic model of character refinement as the key to achieving one’s highest potential (Self-Actualization). Islam designates human beings as Allah’s viceregents on Earth, yet this status is not inherent; it is realized through a structured process of moral and spiritual growth. Drawing from Islamic thought, particularly Rumi’s Universal Man and Iqbal’s Mard-i-Momin, we argue that personal perfection is not just an abstract or metaphysical state but a measurable and attainable goal. This theory integrates the Ruh (Soul), Qalb (Heart), and Nafs (Self) as essential faculties in character formation, positioning Husn-i-Akhlaaq as playing a pivotal role in this holistic framework for personality development. We hypothesize that this model not only fosters spiritual excellence but also has direct implications for psychological resilience, emotional wellbeing, and overall human flourishing. By bridging Islamic teachings with contemporary psychological discourse, this article advances a structured, interdisciplinary approach to character education and character development, emphasizing its potential applications in physical health, mental health, personal growth, and social transformation.